Mapeamento do potencial eólico de micro e minigeração do município de Cascavel - PR. - Guicho, Ricardo (2019)
The importance of the hydraulic generation in the Brazilian electrical matrix related to hydric crisis (2014-2015) demands decentralization from this generation source. The search for renewable sources has become fundamental for sustainable development, and aeolian energy at low heights has gained space, since the Normative Resolution from the Agência Nacional de Energia Elétrica nº 482/2012 favored micro and minigeneration. The aeolian potential of Cascavel-PR was plotted from the data obtained by the Sistema Meterológico do Paraná (SIMEPAR), using a historical series of 21 years (1997-2017). It was possible to identify the climatological profile with wind direction predominance, besides estimated speeds in different heights. For classification of soil use and occupation, and creation of the algorithm using the software Spring 5.4.2, it was used an image of Cascavel-PR image obtained from the satellite Sentinel-2. The software Surfer 15 was used to the kriging of the data acquire from SIMEPAR, and the software OGis 2.14 for production of thematic letters. Geoprocessing was conducted in the Geoprocessing Lab (LabGeo) from the Universidade Tecnológica Federal do Paraná (UTFPR), Campo Mourão Campus, and the creation of maps was conducted in the Topography and Geoprocessing Lab (GeoLab) from Universidade Estadual do Oeste do Paraná (UNIOESTE), Cascavel Campus. From the semiautomatic classification, five pre-determined classes were obtained, which were used for speed and potential calculations, in which the maximum speeds varied from 9 to 19 m.s-1 generating from 488 to 2986 Watts. For average speeds, speeds varied from 3 to 6 m.s-1, generating 18 to 87 Watts. The wind predominance identified in Cascavel was identified as coming from Northeast (NE). October at 40 m height presented highest estimated potential, reaching 19 m.s-1 and being able to generate up to 2986 Watts in maximum speed. Spring season was considered the best seasonal period at 40 m height for Cascavel aeolian potential.